Faktor-Faktor Yang Mempengaruhi Tingkat Kemiskinan di Kabupaten Polewali Mandar - Ulva Ulva; Abd Rahim; Sri Astuty; Diah Retno Dwi Hastuti; Abdul Rajab (Jurnal Ekonomi-Qu, 2025)
This study aims to examine the influence of Economic Growth, Population, Human Development Index (HDI), and Income Inequality on Poverty Levels in Polewali Mandar Regency during the period 2014–2023. The results of the study indicate that Economic Growth has a statistically significant negative effect on poverty, indicating that improving economic performance can significantly reduce poverty levels. The Population variable shows a positive but not statistically significant relationship, meaning that demographic growth does not have a direct impact on poverty. The HDI shows a significant positive association, reflecting the complex relationship between human development and poverty incidence. In contrast, Income Inequality shows a negative correlation with poverty, a result that contradicts conventional economic theory. These findings emphasize the need for a more integrated and comprehensive strategy in poverty alleviation efforts. Therefore, it is recommended that the Polewali Mandar Regency Government formulate a development strategy that focuses on improving the quality of human resources, promoting equitable income distribution, and developing inclusive and sustainable economic growth, to address poverty more effectively.